The appearances deceive: change and metamorphosis in the Odyssey (Circe de clásicos y modernos, 2018)
In the Odyssey there are frequent occasions for disguise and dissimulation. Considering anonymity a peculiar case of disguise, Ulysses often disguises himself, making this a distinctive part of his personality. Of a different nature, metamorphosis is also a common phenomenon in the poem and in Greek mythology. Gods transform themselves and have the power to modify other beings, affecting their corporal nature by radical transformations. We explore metamorphosis’s categories and functions in the Odyssey, how it helps constructing divine and human characters and how it influences weaving the poem’s action.
Keywords: Odyssey; metamorphosis; epiphany; disguise; theatricality